The gingival condition of oral contraceptives users at desa Hegarmanah, Kecamatan Jatinangor - Sibuea, Miduk; Hendiani, Ina; Rusyanti, Yanti (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2010)
The change of hormonal condition is a systemic condition that affected the periodontium condition. Oral contraceptives is one of the systemic risk that can change hormonal condition. The purpose of the research was to evaluate gingival condition of oral contraceptives users and to find the difference of gingival condition between users and non users of oral contraceptives at Desa Hegarmanah, Kecamatan Jatinangor. The research method was descriptive analytic with purposive sampling, consist of 69 users and 30 non users of oral contraceptives. The gingival condition was scored by using Loe and Sillnes gingival index. The research showed that the average of gingival index in oral contraceptives users was 1.913 and non users was 1.707. The statistic analysis was U Mann Whitney non parametric test and the Î± was 5% showed that there was a significant difference of gingival condition between users and non users of oral contraceptives. The conclusion of the research was the gingival condition of oral contraceptives users was different with non users at Desa Hegarmanah Kecamatan Jatinangor but clinically was the same, that is in moderate gingivitis category.